DAMPAK PEMASARAN DIGITAL TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Haryadi, Wahyu; Ady, Sri Utami; Sayidah, Nur (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
The use of digital marketing is an efficient means to open new marketing channels for MSME products. The purpose of this study is to fill the gap in previous research by analyzing the impact of digital marketing on the income of micro, small and medium enterprises (MSMEs) in Sumbawa Regency. This type of research is a comparative study with a quantitative approach. Data collection techniques through questionnaires and documentation. The number of samples in this study was 30 MSME samples that used digital marketing media and 30 MSME samples that did not use digital marketing. The results of the Kolmogorov Test stated that the data was normally distributed. The results of the study showed that there was a difference in average income between MSMEs that used digital marketing and MSMEs that did not use digital marketing. The results of this study prove that product marketing using digital marketing has an impact on increasing MSME income in Sumbawa Regency